Convergence Theorem for a Family of New Modified Halley's Method in Banach Space. (17th June 2014) - Lin, Rongfei; Zhao, Yueqing; Wu, Qingbiao; Hu, Jueliang
Abstract : We establish convergence theorems of Newton-Kantorovich type for a family of new modified Halley's method in Banach space to solve nonlinear operator equations. We present the corresponding error estimate. To show the application of our theorems, two numerical examples are given.